천연 식물 추출물의 항염 효과가 in vitro 반추위 발효성상과 메탄 생성에 미치는 영향 - 이신자; 이수경; 임정화; 손창준; 이성실; Shin Ja Lee; Su Kyoung Lee; Jung Hwa Lim; Chang Jun Son; Sung Sill Lee (농업생명과학연구, 2017)
본 시험은 항염에 효과가 있다고 알려진 식물 추출물의 첨가가 반추위 발효와 메탄 생성에 미치는 영 향을 알아보기 위해 in vitro 실험을 수행하였다. 항염과 항산화 효과가 있는 산뽕나무, 뽕나무, 예덕나 무, 오동나무, 방아풀과 은행나무 6종을 선발하였다. 반추위액과 McDougall buffer 혼합액 15mL과 티 모시 0.3g, 각각의 추출물을 기질의 5%로 넣고 39℃에서 3, 9, 12, 24, 48 그리고 72시간 배양하였다. 항염 효과가 있는 식물 추출물의 첨가는 반추위 발효 성상(pH, 건물소화율, Glucose 농도, 암모니아 농도, 단백질 농도, 미생물 성장량, 휘발성지방산)에는 영향을 미치지 않았다. 총 가스 발생량은 각기 다른 양상을 보였으며, 이산화탄소 발생량은 48시간대에서 예덕나무와 방아풀에서 대조구에 비해 유의 적(p<0.05)으로 높았다. 또한 메탄 발생량은 배양 초기에는 대조구보다 첨가구에서 유의적(p<0.05)으로 감소하였으나, 발효가 진행될수록 대조구에 비해 첨가구에서 더 많은 메탄이 발생하였다. Polyphenol과 flavonoid는 은행나무 추출물구에서 가장 높았다. 본 시험의 결과에서 항염에 효과가 있는 식물 추출물 을 in vitro 반추위 배양액에 첨가하였을 때, 반추위 발효에는 영향을 미치지 않았고, 메탄은 초기 발효 에 저감 효과가 있는 것으로 사료된다. This study was conducted to investigate the effects of anti-inflammatory plant extracts on the in vitro rumen fermentation characteristics and methane emission. Anti-inflammatory plant extracts from Morus bombycis Koidz, Mallotus japonicus L., Morus alba L., Paulownia coreana Uyeki, Isodon japonicus Hara and Ginkgo biloba L. were used in the study. The ruminal fluid(5 mL), McDougall buffer(10 mL), timothy as a substrate(0.3 g) and each anti-inflammatory plant extract(5% of substrate) were dispensed anaerobically into 50mL serum bottle. The mixtures were incubated for 3, 9, 12, 24, 48 and 72h at 39℃ without shaking. Supplementation of the anti-inflammatory plant extracts did not effects characteristics(pH, digestibility of dry matter, glucose concentration, ammonia concentration, protein concentration, VFA) on rumen fermentation. Total gas was showed a different pattern depending on treatments. Carbon dioxide was significantly(p<0.05) higher in Morus alba and Isodon japonicus than in control at 48h. Methane was significantly(p<0.05) lower in treatment than in control at initial fermentation. However the more incubation time was increased, the more methane emission was higher in treatment than in control. The concentrations of polyphenol and flavonoid were higher in Ginkgo biloba. In conclusion, supplementation of the anti-inflammatory plant extracts did not effect on rumen fermentation and methane emission was decreased in initial fermentation.